Slavery's capitalism : a new history of American economic development - Beckert, Sven; Rockman, Seth (Early American studies., 2016)
Slavery's Capitalism explores the role of slavery in the development of the U.S. economy during the first decades of the nineteenth century. It tells the history of slavery as a story of national, even global, economic importance and investigates the role of enslaved Americans in the building of the modern world.